Differential impact of metabolic syndrome on subclinical atherosclerosis according to the presence of diabetes - Won, Ki-Bum (BioMed Central, 2013)
BACKGROUND: Metabolic syndrome (MS) is associated with increased risks of diabetes and atherosclerotic cardiovascular disease. However, data on the impact of MS and its individual components on subclinical atherosclerosis (SCA) according to diabetes status are scarce. METHODS: Surrogate markers of SCA, brachial–ankle pulse wave velocity (baPWV), and carotid intima–medial thickness (IMT) and plaque were assessed in 2,560 subjects (60 ± 8 years, 33% men) who participated in baseline health examinations for a community-based cohort study. RESULTS: The participants included 2,149 non-diabetics (84%) and 411 diabetics (16%); 667 non-diabetics (31%) and 285 diabetics (69%) had MS, respectively. Diabetics had significantly higher baPWV and carotid IMT, and more plaques than non-diabetics (p < 0.001, respectively). Individuals with MS had significantly higher baPWV and carotid IMT than those without MS only among non-diabetics (p < 0.001, respectively). Among MS components, increased blood pressure was significantly associated with the exacerbation of all SCA markers in non-diabetics. The number of MS components was significantly correlated with both baPWV and carotid IMT in non-diabetics (baPWV: r = 0.302, p < 0.001; carotid IMT: r = 0.217, p < 0.001). Multiple regression showed both MS and diabetes were significantly associated with baPWV (p < 0.001, respectively), carotid IMT (MS: p < 0.001; diabetes: p = 0.005), and the presence of plaque (MS: p = 0.041; diabetes: p = 0.002). CONCLUSIONS: MS has an incremental impact on SCA in conditions without diabetes. The identification of MS and its individual components is more important for the risk stratification of CVD in non-diabetic individuals.